Corporate social responsibility and dimensions of performance: An application to U.S. electric utilities. (October 2017) - Ait Sidhoum, Amer; Serra, Teresa
Abstract: This paper investigates the relationships among performance dimensions associated with corporate social responsibility (CSR) focusing on the U.S. electric utility sector. Results of a statistical copula approach suggest that economic performance of utilities is compatible with environmental, social, and governance performance, The CSR model has the potential to help U.S. electric utilities become better corporate citizens. Highlights: We assess link among economic and CSR performance in US electric utility sector. A copula approach is used to model the dependency relationships. A positive association is reported between economic and CSR performance. The three links studied show an increasing trend over the studied period. The lower tail dependence is much stronger than that of the upper tail.